Cricotracheal resection for adult subglottic stenosis: Factors predicting treatment failure. (9th September 2019) - Jethwa, Ashok R.; Hasan, Wael; Palme, Carsten E.; Mäkitie, Antti A.; Espin‐Garcia, Osvaldo; Goldstein, David P.; Gilbert, Ralph W.; Keshavjee, Shaf; Pierre, Andrew; Gullane, Patrick J.
Abstract : Objectives/Hypothesis: Identify predictors of decannulation failure after cricotracheal resection (CTR) and thyrotracheal anastomosis (TTA) in patients with subglottic stenosis (SGS). Study Design: Retrospective cohort study. Methods: Charts of patients undergoing CTR and TTA for SGS at the University Health Network, Toronto, Ontario, Canada between 1988 and 2017 were reviewed. Patient, pathology, treatment, and outcome data were collected. The end points for statistical analysis were development of restenosis and permanent tracheostomy. Results: One hundred fourteen patients (n = 114) were eligible for inclusion in this review. The mean age at primary resection was 46.9 years, 95 (83%) were females, and 19 (17%) were males. The rate of restenosis and permanent tracheostomy was 13% and 5%, respectively. Sixty‐two patients (54%) underwent a CTR and TTA, and 52 patients (46%) underwent a CTR, laryngofissure, and TTA. Traumatic stenosis (odds ratio [OR] = 10.3, P = .017), longer T‐tube duration (OR = 1.2, P = .011), combined glottic/subglottic stenosis (OR = 10.47, P = .010), start of the stenosis at the vocal cords (OR = 6.6, P = .029), postoperative minor complications (OR = 13.6, P = .028), and need for repeat surgery (OR = 44.1, P < .001) were associated with an increased risk of requiring permanent tracheostomy. Conclusions: CTR and TTA are excellent surgical approaches for adult patients with subglottic stenosis. In this study, 5% of patients required permanent tracheostomy. Factors predicting treatment failure include traumatic stenosis, longer T‐tube duration, combined glottic/subglottic stenosis, start of stenosis at the level of vocal cords, postoperative minor complications, and need for repeat surgery. Level of Evidence: 4 Laryngoscope, 130:1634–1639, 2020